A cross sectional analysis of SME failure within the industrial sector: focus on IDC funded investments - Amparbeng, Kofi (Research of GSB, 2018)
Small and Medium Enterprises play an important economic role in many countries. In South Africa, for example, a significant proportion of the formal business entities are SMEs; and they contribute between 52 and 57% to GDP, and provide about 61% to employment. However, despite their significance in the local economy, SMEs regularly encounter the threat of failure. Business failure can be disruptive and costly to a large number of stakeholders, which include the owner, the employees, suppliers, customers, investors, bankers, communities, etc. This study examines failed SMEs and compares them with SMEs that are going concerns in order to discover significant differences between the two groups. The study adopted non-parametric tests and binary logistic regression methods. The final data set included 50 failures covering the calendar years July 2009 and June 2012, and 50 going concerns listed in the IDC database on 30 June 2012. The dataset was limited to industrial sector firms from the Chemicals, Metal, Textiles and Wood & Paper industry. The results of this study indicate that, the going concern sample of SMEs were larger than the failures in terms of firm size; led by more experienced management; older in terms of years in existence; and were supported by a stronger equity structure and interest cover ratio. The binary logistic regression results also show that SMEs located in provinces with high per capita income are associated with high probability of failure. But SMEs with increase in annual turnover or increase in equity structure are less likely to fail. Understanding which variables are statistically significantly different between the two groups can enable business owners to develop plans to increase their likelihood of survival. They can also help other stakeholders such as funders implement policies and controls for funding SMEs that mitigate these risk factors.